Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation